2021
DOI: 10.1101/2021.03.02.433653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic independence drives gut microbial colonization and resilience in health and disease

Abstract: A detailed understanding of gut microbial ecology is essential to engineer effective microbial therapeutics and to model microbial community assembly and succession in health and disease. However, establishing generalizable insights into the functional determinants of microbial fitness in the human gut has been a formidable challenge. Here we employ fecal microbiota transplantation (FMT) as an in natura experimental model to identify determinants of microbial colonization and resilience. Our long-term sampling… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 122 publications
3
40
0
Order By: Relevance
“…By contrast, adults have a microbiome that is relatively resistant to colonization with new organisms even after perturbation by antibiotics [19][20][21] . While adults living in the same household or in close-knit communities may have more similar microbes than those outside the group 22 , to our knowledge, direct transmission of gut microbes between adults has not been observed with high-resolution metagenomic methods, with the notable exception of fecal microbiota transplantation [23][24][25] , a drastic reshaping of the gut microbiota often used in response to Clostridiodes difficile infection. Transmission of gut microbiota is thought to occur by a fecal-oral route, which could happen in the hospital environment by exposure to contaminated surfaces or equipment, sharing a room or bathroom, contaminated hands of healthcare workers or other sources.…”
Section: Introductionmentioning
confidence: 80%
“…By contrast, adults have a microbiome that is relatively resistant to colonization with new organisms even after perturbation by antibiotics [19][20][21] . While adults living in the same household or in close-knit communities may have more similar microbes than those outside the group 22 , to our knowledge, direct transmission of gut microbes between adults has not been observed with high-resolution metagenomic methods, with the notable exception of fecal microbiota transplantation [23][24][25] , a drastic reshaping of the gut microbiota often used in response to Clostridiodes difficile infection. Transmission of gut microbiota is thought to occur by a fecal-oral route, which could happen in the hospital environment by exposure to contaminated surfaces or equipment, sharing a room or bathroom, contaminated hands of healthcare workers or other sources.…”
Section: Introductionmentioning
confidence: 80%
“…Genome W0 originated from the pre-FMT sample, whereas genomes W1 and W48 originated from 1-week and 48-weeks a ter FMT. e previous analysis of these data concluded that Akkermansia W0 is replaced by Akkermansia W1 a ter FMT and persisted in the recipient for at least 48 weeks 36 . Indeed, the genomes W1 and W48 resolved to Akkermansia muciniphila, and the pairwise genome-wide average nucleotide identity (gANI) between them was over 99.9%, confirming that these genomes likely represent the same population.…”
Section: Real Bacterial Nanopore Long-reads Corrected With DI Ferent Reference Databasesmentioning
confidence: 93%
“…Akkermansia population W1 that replaces W0 is also reconstructed from Illumina short reads and named as DA_MAG_00110 in the original study 36 . We used Flye v2.6 -which includes one round of long-read consensus polishing -for long-read assembly 20 , Pilon v1.23 for short-read polishing 38 , and proovframe v0.9.6 for frame-shi t correction.…”
Section: Mycoplasma Bovis Reads Corrected With Uniref90 Proteins Of DI Ferent Amino-acid Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Published across thirteen distinct studies, FMT was used to treat recurrent Clostridioides difficile infection (rCDI) (Watson et al 2021;Smillie et al 2018;Song et al 2013) (Podlesny et al, submitted), type 2 diabetes mellitus, obesity and metabolic syndrome (MetS) (Li et al 2016;Ng et al 2021;Wilson et al 2021), the inflammatory bowel diseases Crohn's disease and ulcerative colitis (IBD) (Kong et al 2020;Paramsothy et al 2019;Kump et al 2018), to eradicate multidrug-resistant Enterobacteriaceae carriage (MDR) (Bar-Yoseph et al 2020;Leo et al 2020), and to induce response to anti-PD-1 immunotherapy in immune checkpoint inhibitor therapy-refractory melanoma patients (ICI) (Davar et al 2021;Baruch et al 2021).…”
Section: Study Cohortmentioning
confidence: 99%